A Theological Implication of ‘Humility’ in Mark 10: 13-16 from the Perspective of the Parable of the Kingdom of God - Halim Wiryadinata (Sekolah Tinggi Teologi Torsina Surakarta, 2018)
The parable of the Kingdom of God brings the seriousness of studying about the meaning of what the Lord Jesus Christ wants to say. There are many arguments to say about the meaning of the Kingdom of God, while a new approach of the twentieth century appears. The study of historical Jesus by N. T Wright gives the idea of Jesus, Israel, and the Cross. If the parable of the Kingdom of God is retelling the story of Israel, then the new concept of the Kingdom of God should be different from the old Israel. The concept of humility should be seen as the way out of the Kingdom of God. Mark 10: 13 – 16 where the Lord Jesus Christ uses the concept of the little children, it apparently shows the helplessness and humility concepts as the way out for the Kingdom of God. However, the concept of humility should be seen as the proclamation of the Kingdom of God in the perspective of a mission to the people. Finally, the concept of humility also should not beyond the limitation of the Gospel. It should be in the line of the meaning of the Gospel itself. We are encouraged not to repeat what history happens, but rather to learn from the history of Liberation Theology.